Attention to the diversity of minors in conflict with criminal law from an integrative perspective - Chaviano Jiménez, Aldo (2021)
Responding to the needs of professional and human improvement by attending to diversity is one of the demands of educational systems. International studies carried out by several authors have shown concerns about the attention to minors in conflict with the law. The objective of this work refers to a review study by different professionals of the world, about the attention received by minors in conflict with the criminal law, as well as the causes that originate it, lines of work and strategies to be developed for their prevention and attention at all levels from the intersectoriality.